Isolation of Serratia marcescens in a surgical wound - Ledys Pérez Morales; Yenisbel Valdivia Portales; Acelia Torres Morel (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Serratia marcescens is a Gram possitive bacila, facultative anaerobic, negative oxidase, belonging to the enterobacteriaceae family. It is presented as a nosocomial agent and the person to person transmission is the most important way of dissemination. Its isolation is uncommon, reason for which it was decided to present the case of a 32 year old patient, with healthy antecedents, from a rural area and a 35 week pregnancy that developed without apparent obstetric risks. She was referred to the General University Hospital University Dr. Gustavo Aldereguía Lima with recurrent abdominal pain of three hours, vomiting with food remains and 38 degree fever. She was performed a surgery due to appendicitis and she was discharged in a good condition, but on the day seven she had a dehiscence in the surgical wound and it was observed a yellowish discharge from it. She was admitted again and Serratia marcensens was isolated. After treatment she had a satisfactory evolution.